2022
DOI: 10.48048/tis.2022.2192
|View full text |Cite
|
Sign up to set email alerts
|

Production of Hyaluronic Acid from Molasses by Streptococcus thermophilus TISTR 458

Abstract: The purpose of this study was to investigate the capability of Streptococcus thermophilus TISTR 458 on hyaluronic acid (HA) production by using various carbon sources including glucose, sucrose and sugarcane molasses. HA production was determined using a turbidity assay by precipitation with cetyltrimethylammonium bromide (CTAB) and the sugar content was analysed by a sulphuric acid-UV spectrophotometry method. The results showed that S. thermophilus TISTR 458 produced the maximal yield of HA from glucose, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In this way, an HA yield of 30 g/L was successfully attained [ 88 ]. Another strategy showed that as an alternative to glucose, molasses could be used as a carbon source in the fermentation medium of S. zooepidemicus [ 89 ]. Indeed, the presence of this alternative and cheaper sugar allowed an increase in the yield of the HA up to 0.2 g/L compared to standard conditions (43 mg/L) [ 89 ].…”
Section: Ha Fermentation Process In Engineered Host Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, an HA yield of 30 g/L was successfully attained [ 88 ]. Another strategy showed that as an alternative to glucose, molasses could be used as a carbon source in the fermentation medium of S. zooepidemicus [ 89 ]. Indeed, the presence of this alternative and cheaper sugar allowed an increase in the yield of the HA up to 0.2 g/L compared to standard conditions (43 mg/L) [ 89 ].…”
Section: Ha Fermentation Process In Engineered Host Microorganismsmentioning
confidence: 99%
“…Another strategy showed that as an alternative to glucose, molasses could be used as a carbon source in the fermentation medium of S. zooepidemicus [ 89 ]. Indeed, the presence of this alternative and cheaper sugar allowed an increase in the yield of the HA up to 0.2 g/L compared to standard conditions (43 mg/L) [ 89 ]. In addition to the pH, the incubation temperature, agitation speed, soil composition, and size of inoculum are key parameters of the fermentation process that affect the yield of the final product.…”
Section: Ha Fermentation Process In Engineered Host Microorganismsmentioning
confidence: 99%